The multilingual challenge : cross-disciplinary perspectives - Jessner, Ulrike; Kramsch, Claire J. (Trends in applied linguistics, 2015)
This collection of scholarly articles is the first to address the challenges of multilingualism from a multidisciplinary perspective. The contributors to this volume examine both the beneficial and the problematic aspects of multilingualism in various dimensions, that is, they address familial, educational, academic, artistic, scientific, historical, professional, and geopolitical challenges.